Distributed generation: A review on current energy status, grid-interconnected pq issues, and implementation constraints of dg in malaysia - Lee J.Y.; Verayiah R.; Ong K.H.; Ramasamy A.K.; Marsadek M.B. (MDPI AG, 2023)
Fossil fuel power plants; Fossil fuels; Planning; Power quality; Renewable energy resources; Sustainable development; Contributing factor; Distributed generation technologies; Issues and challenges; Power quality problem; Power system networks; Reliable energy services; Renewable energy generation; Renewable technology; Distributed power generation